Analisis Proyeksi Laporan Keuangan Perusahaan Penerbangan Saat Transisi PSAK 30 Menjadi PSAK 73 - Laksana, Mahardika Putra; Sudradjat, Sudradjat (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
The aim of this research is to anticipate the emergence of a new regulation in accounting studies. Especially the emergence of PSAK 73 that will succeed PSAK 30 in terms of Leasing. This research gives the projection if a new regulation is in effect. PSAK 73 changes the form of double accounting system into a single one, meaning that lease is not being classified and calculated with two methods like capital lease and operating lease. It’s using capital lease calculation with it being classified as right of use asset. Asset is being recognized and depreciation expense follows after with interest. The result of this research shows that, the trantition of PSAK 30 to PSAK 73 affects entity’s income statement. Entity’s expenses increase because of the additional interest and depreciation expense. Assets also increase resulting in management asset ratio and profitability ratio to fall. Keywords: PSAK 30, PSAK 73, Transition, Asset of Use